Energy Policy Evolution in Pakistan: Balancing Security, Efficiency, and Sustainability - Qaisar Shahzad; Kentaka Aruga (Energies)
This study analyzes the evolution of Pakistan’s energy policies from 1990 to 2024, documenting their transition from a singular focus on generation capacity to an integrated approach prioritizing renewable energy and efficiency. Through a systematic literature review of 110 initially screened studies, with 50 meeting the inclusion criteria and 22 selected for in-depth analysis, we evaluated policy effectiveness and identified implementation barriers. Our methodology employed predefined criteria focusing on energy efficiency, environmental sustainability, and climate impact, utilizing the Web of Science and Scopus databases. Early policies like the National Energy Conservation Policy (1992) and the Energy Policy (1994) emphasized energy security through generation capacity expansion while largely neglecting renewable sources and efficiency improvements. The policy landscape evolved in the 2000s with the introduction of renewable energy incentives and efficiency initiatives. However, persistent challenges include short-term planning, inconsistent implementation, and fossil fuels dependence. Recent framework like the Alternative and Renewable Energy Policy (2019) and the National Energy Efficiency and Conservation Plan (2020–2025) demonstrate progress toward sustainable energy practices. However, institutional, financial, and regulatory barriers continue to constrain effectiveness. We recommend that Pakistan’s energy strategy prioritize the following: (1) long-term planning horizon; (2) enhanced fiscal incentives; and (3) strengthened institutional support to meet global energy security and climate resilience standards. These measures would advance Pakistan’s sustainable energy transition while supporting both energy security and environmental objectives.